2014
DOI: 10.2298/vsp120418006l
|View full text |Cite
|
Sign up to set email alerts
|

Surface enlargement of a new arterialised venous flap by the surgical delay method

Abstract: Analysis of previous experimental models on the rabbit ear, non-delayed and delayed (to enlarge flap surface) led us to conclusion that previously created experimental models of non-delayed AVF are hemodynamically negative. Our experimental non-delay AVF model is hemodynamically more positive than previously created models of non-delay AVF and provides better conditions for AVF survival and enlargement of vital flap surface of elevated flap. On the other hand, surgical delay method significantly enlarges vital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…[ See Table, Supplemental Digital Content 2 , which shows the summary of the studies on unconventional perfusion flaps in experimental animal models identified in the systematic review and included in the meta-analysis. 12,17,20,41,43,49-111 For each study, the optimized experimental animal model is identified, along with its characteristics. These experimental models were those that presented better flap survival rates in each published article ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ See Table, Supplemental Digital Content 2 , which shows the summary of the studies on unconventional perfusion flaps in experimental animal models identified in the systematic review and included in the meta-analysis. 12,17,20,41,43,49-111 For each study, the optimized experimental animal model is identified, along with its characteristics. These experimental models were those that presented better flap survival rates in each published article ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Half of the identified articles were published until 1994, and three-quarters of these were published until 2003. Studies were performed in 20 different countries 12,17,20,41,43,49-111 (cited in Table, Supplemental Digital Content 2 , http://links.lww.com/PRS/D415). The most commonly used animal species was the rabbit (57.1 percent), followed by the rat (26.4 percent), the dog (14.3 percent), and the pig (2.2 percent).…”
Section: Resultsmentioning
confidence: 99%